Scoping review of qualitative studies investigating reproductive health knowledge, attitudes, and practices among men and women across Rwanda. - Julie M Buser; Ella August; Gurpreet K Rana; Rachel Gray; Olive Tengera; Faelan E Jacobson-Davies; Madeleine Mukeshimana; Diomede Ntasumbumuyange; Gerard Kaberuka; Marie Laetitia Ishimwe Bazakare; Tamrat Endale; Yolanda R Smith (PLoS ONE)
Background Research efforts in Rwanda to improve sexual and reproductive health and rights (SRHR) are increasing; however, comprehensive literature reviews on SRHR are limited. This scoping review examines individual and contextual factors shaping knowledge, attitudes, and practices in the domains of: 1) family planning, 2) abortion care, and 3) other SRHR in Rwanda. Recognizing that individual, community, and societal factors influence RH, this review is guided by Bronfenbrenner's Ecological Systems Theory. Methods Eligible studies were conducted in Rwanda, included males and/or females of any age, and were published within the past 20 years. Studies reporting views of only healthcare or other professionals were excluded. Results Thirty-six studies were included. The majority addressed individual and contextual considerations. At the individual level, studies explored knowledge about SRHR problems while at the interpersonal level, the support and attitudes of men and community members for adolescent SRHR were investigated. In terms of healthcare organization, maternal health practices, increased access to family planning programs, and the need for sexually transmitted infection programs was explored. At the social and cultural level, researchers investigated beliefs and traditional gender roles. Regarding public health policy, studies mentioned promoting and increasing funding for SRHR and reducing gender inequities. Conclusion Our findings can inform SRHR research programs, public health campaigns, and policy advances in Rwanda.